Outcomes of a pilot evaluation of a group urotherapy programme for children with complex elimination disorders: An Australian experience. (September 2022) - Peck, Blake; Terry, Daniel; Martin, Benita; Matthews, Belinda; Green, Andrea
Evidence-based interventions have continued to show positive effects on both reducing symptoms and helping children with elimination disorders achieve continence and manage troubling psychological distress. Despite this, there is a group of children who do not respond to standard treatments and are classified as having a complex elimination disorder. As a means of addressing the broader clinical challenge and implications of complex elimination disorders, a team of clinicians in Germany developed the Urinary and Faecal Incontinence Training Program for Children and Adolescents. A pilot investigation was undertaken to apply the Urinary and Faecal Incontinence Training Program for Children and Adolescents programme to children aged 6–12 years in an Australian context who met the complex elimination disorder diagnostic criteria, to determine if any subsequent change in the measures of life quality and general well-being was achieved. Findings suggest a reduction in the frequency of the child's symptoms and improvements in family quality of life measures. Qualitatively, children and parents perceived that their child's ability to now respond to stimuli and in so doing avert severe accidents was a major outcome of the programme and was able to increase a child's sense of acceptance of incontinence, improve levels of self-efficacy and increase self-awareness.